1990
DOI: 10.1093/jmedent/27.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Culex torrentium and Cx. pipiens (Diptera: Culicidae) as Experimental Vectors of Ockelbo Virus

Abstract: The ability of the sibling species Culex pipiens (L.) and Culex torrentium (Martini) from central Sweden to transmit Ockelbo (OCK) virus was determined. Both species became infected after ingesting OCK virus from a viremic chicken; they transmitted this virus to chickens after 21-28 d of extrinsic incubation. In Cx. torrentium, infection rates were 90% or higher, and all 10 refeeding mosquitoes transmitted virus after feeding on chickens with a viremia of at least 10(3.0) plaque-forming units (PFU)/ml. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 0 publications
3
50
1
1
Order By: Relevance
“…Similar results are reported for Culex tarsalis (western equine encephalitis virus), 26 Culex torrentium (Okelbo virus), 27 and for Ae. albopictus (chikungunya virus) 28 in which mosquitoes became infected when fed on hosts with undetectable viremias.…”
Section: Resultssupporting
confidence: 86%
“…Similar results are reported for Culex tarsalis (western equine encephalitis virus), 26 Culex torrentium (Okelbo virus), 27 and for Ae. albopictus (chikungunya virus) 28 in which mosquitoes became infected when fed on hosts with undetectable viremias.…”
Section: Resultssupporting
confidence: 86%
“…We have previously shown that adult birds of these three species produce Sindbis viremias several magnitudes higher than required to infect the enzootic vector species Cx. torrentium (Lundströ m et al 1990(Lundströ m et al , 1993. In Sweden, these Turdus species produce two to four clutches of nestlings during the breeding season, and the season extends from April through July.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, these are Culex pipiens, Culex torrentium (principal enzootic vector in Sweden), Culiseta morsitans, Coquillettidia richiardii, Ochlerotatus communis, Ochlerotatus excrucians, Aedes cinereus, and Anopheles hyrcanus (Berezin et al 1972;Francy et al 1989;Lundström et al 1990a, b;Turell et al 1990;Lvov et al 1984Lvov et al , 1985. Laboratory transmission of SINV was documented also in Aedes albopictus (Dohm et al 1995).…”
Section: Mosquito-borne Human Pathogenic Viruses Autochthonous In Europementioning
confidence: 99%